Clinical case of pregnancy complicated by thrombotic thrombocytopenic purpura - M. V. Semenova; D. D. Sarrakhov; A. R. Gilimkhanova; A. R. Kamalova; P. G. Vakhitov; А. A. Musina; B. A. Islamgaraev (Acta Biomedica Scientifica, 2024)
Background. Thrombotic thrombocytopenic purpura is a rare blood disease characterized by increased thrombogenesis in the microcirculation. One of the most common triggers for the development of this disease is pregnancy. The article describes a case of pregnancy complicated by thrombotic thrombocytopenic purpura.Materials and methods. To assess the clinical case, we used a retrospective analysis of medical documentation: maternity case record, birth history, results of laboratory and instrumental research methods.Results. A 32-year-old patient was admitted to hospital at week 32 of gestation with manifestations of moderate preeclampsia, thrombocytopenia, and moderate anemia. Due to worsening of the condition, the delivery was performed by cesarean section. Subsequently, the mother’s condition did not improve: thrombocytopenia and hyperbilirubinemia progressed; the level of transaminases increased; ADAMTS13 activity was 8 %. Teleconferences were repeatedly held with experts from the National Medical Research Center for Obstetrics, Gynecology and Perinatology named after Academician V.I. Kulakov (Moscow). Complex therapy including extracorporeal methods led to a positive result; the patient was discharged in satisfactory condition under the supervision of a hematologist and obstetrician-gynecologist.Conclusion. Thrombotic thrombocytopenic purpura treatment tactics have its own characteristics; it is necessary to diagnose this pathology in a timely manner to provide qualified medical care and to prevent maternal and perinatal losses.